Segmental Dilation of the Colon: Support for a Muscle Wall Etiology - David J. Waldron; Kenneth L. Bowes; Laurence D. Jewell (Canadian Journal of Gastroenterology)
A patient with segmental dilatation of the colon who presented with chronic constipation is reported. A review of previous cases of this rarely reported condition and the typical features of the disorder is presented. A possible contributing factor to its etiology is proposed on the basis of a pathological appearance of the colonic muscle wall not previously described.